Self-Efficacy and Punishment Drive Employee Performance in Indonesia - Dewi Rojiyah; Sumartik (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the effects of self-efficacy, reward, and punishment on employee performance at Pok-Pok My Crispy Snack in East Java, Indonesia. Using a quantitative approach and a sample of 60 employees, data were collected via questionnaires and analyzed with SPSS 22. Results show that self-efficacy and punishment significantly impact employee performance, while reward does not. Self-efficacy, reward, and punishment together significantly influence performance. These findings highlight the importance of boosting self-efficacy and appropriately applying punishment to enhance employee performance, while suggesting a re-evaluation of reward strategies. Highlight: Self-efficacy significantly impacts employee performance. Reward does not significantly affect performance. Combined, self-efficacy and punishment improve performance. Keywoard: Self-efficacy, Reward, Punishment, Employee performance, Quantitative research